2008
DOI: 10.3922/j.psns.2008.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell grafts as therapeutic tools for central nervous system disorders.

Abstract: The last few years have seen a growing interest in stem cell research. The media has helped to keep attention to the subject making it as popular as therapeutic cloning. A number of studies highlighted the importance of stem cells as prospective therapy for neurodegenerative conditions. The possibility of successful treatment for such pathologies using stem cells has raised enormous hope. Whilst in some countries biotechnologists have realised the commercial potential of the field, human stem cell research and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 102 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Several experiments have demonstrated that SCs' grafts ameliorate a variety of CNS conditions. However, crucial issues such as functional connectivity, in vivo differentiation and survival, potential for migration to areas of lesion, host's immune reactions or mechanisms regulating these functions, are still to be addressed (Oliveira et al, 2008). Existing clinical data suggest that transplantation is technically feasible and can be carried out safely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several experiments have demonstrated that SCs' grafts ameliorate a variety of CNS conditions. However, crucial issues such as functional connectivity, in vivo differentiation and survival, potential for migration to areas of lesion, host's immune reactions or mechanisms regulating these functions, are still to be addressed (Oliveira et al, 2008). Existing clinical data suggest that transplantation is technically feasible and can be carried out safely.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, data on functional outcome and long-term efficiency remains preliminary (Andresa et al, 2008). A greater understanding of the neurobiological and molecular factors that determine the progress of the brain disorder will probably lead to safer treatments (Oliveira et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation